Scopulariopsis sp. and Fusarium sp. in the Documentary Heritage: Evaluation of Their Biodeterioration Ability and Antifungal Effect of Two Essential Oils - Lavin, Paola (2016)
Fungi produce pigments and acids, generating particular local conditions which modify the physicochemical properties of materials. The aims of this work are (i) to investigate bioadhesion, foxing production and biofilm formation by Scopulariopsis sp. and Fusarium sp. isolated from document collections under laboratory conditions; (ii) to verify attack on cellulose fibres and (iii) to study the possibility of reducing fungal growth using natural products. Biofilm formation and extracellular polymeric substance (EPS) production by fungi were demonstrated in laboratory assays and by scanning electron microscopy (SEM) observations. The biocidal activity of two essential oils of Origanum vulgare L. and Thymus vulgaris L. was evaluated using the microatmosphere method. SEM observations showed that these strains were able to attach to paper and form biofilms, causing damage on them, which demonstrates the biodeterioration ability of these microorganisms. Scopulariopsis sp. and Fusarium sp. isolated from paper books showed the formation of fox-like reddish-brown colour spots, attack to the paper structure and pigment production on aged paper samples. The strains tested produced a decrease in the pH of one unit. This would substantiate the effect of the strains in paper biodeterioration. The microatmosphere method showed that volatile compounds of the essential oils have antifungal activity.